An efficient finite element framework for nonlinear seismic soil-foundation-structure interaction in shallow-founded squat masonry structures - Onur Deniz Akan; Massimo Petracca; Guido Camata; Carlo G. Lai; Enrico Spacone; Claudio Tamagnini (Soil Dynamics and Earthquake Engineering, 2026)

A consistent force-based prestressed beam model with curvilinear tendons and bond–slip - Luca Parente; Daniela Addessi; Chin-Long Lee; Enrico Spacone (Engineering Structures, 2026)

Shaking table tests of unreinforced and retrofitted rectangular three-leaf masonry walls under triaxial seismic excitation - Francesco Di Michele; Enrico Spacone; Giuseppe Brando; Guido Camata; Anastasios Sextos; Adam Crewe; George Mylonakis; Matt Dietz; Luiza Dihoru; Humberto Varum (Engineering Structures, 2025)

Simplified model for the seismic performance of masonry infilled RC buildings - Giulia Angelucci; Flavia De Luca; Raffaele De Risi; Fabrizio Mollaioli; Enrico Spacone (Engineering Structures, 2025)

Fiber modelling approach for seismic analysis of flexure-controlled rc columns with ribbed bars calibrated on unidirectional experimental tests - Mariano Di Domenico; Francesca Barbagallo; Marco Terrenzi; Cristina Cantagallo; Paolo Ricci; Guido Camata; Edoardo M. Marino; Enrico Spacone; Gerardo M. Verderame (Bulletin of Earthquake Engineering, 2025)

Sufficiency assessment of intensity measures for natural and spectral-matched ground motion records - Cristina Cantagallo; Raffaele De Risi; Marco Terrenzi; Guido Camata; Enrico Spacone (Bulletin of Earthquake Engineering, 2024)
A correct Intensity Measure (IM) selection is essential for Performance-Based Earthquake Engineering (PBEE) applications, as any probabilistic seismic demand model (PSDM) depends significantly on the IM. If a single IM can describe the complexity of the corresponding ground motion record, it can be defined as sufficient in an absolute sense. However, this is unlikely because a single number should be able to inform on the frequency content, the amplitude, the duration, the energy content, etc. For this reason, literature studies have defined sufficiency in a relative sense to investigate whether one IM is more sufficient (i.e., more informative) than another in predicting the structural response. This work explores the relative sufficiency of eight scalar IMs through Nonlinear Response History Analyses (NRHAs) using two sets of 20 pairs of ground motion records. Both sets are spectrum-compatible and consist of unscaled natural and spectral-matched records. Also, both Cloud and Incremental Dynamic Analysis procedures are used. This study demonstrates that Cloud analysis cannot be used in its conventional form to study sufficiency when spectral-matched accelerograms are used. When natural accelerograms are employed, the results clearly indicate the existence of a sufficient IM among those selected. Conversely, it is more difficult to define the relative sufficiency of the IMs for spectral-matched records because the operation of record adjusting leads to similar structural demands. This result could question either the validity of using spectral-matched accelerograms for PBEE due to the lack of aleatory variability in the structural demand or the necessity of having a sufficient IM when a PSDM is fitted in a PBEE analysis using spectral-matched accelerograms.

Effects of the extended N2 method on non-linear static procedures of reinforced concrete frame structures - Cristina Cantagallo; Marco Terrenzi; Francesca Barbagallo; Mariano Di Domenico; Paolo Ricci; Guido Camata; Enrico Spacone; Edoardo Michele Marino; Gerardo Mario Verderame (Soil Dynamics and Earthquake Engineering, 2023)

A fiber beam element based on plastic and damage models for prestressed concrete structures - Luca Parente; Daniela Addessi; Enrico Spacone (Engineering Structures, 2023)

Influence of the modelling approach on the seismic assessment of RC structures by nonlinear static analyses - Francesca Barbagallo; Mariano Di Domenico; Marco Terrenzi; Cristina Cantagallo; Edoardo Michele Marino; Paolo Ricci; Gerardo Mario Verderame; Guido Camata; Enrico Spacone (Soil Dynamics and Earthquake Engineering, 2023)

Shaking table test and numerical analyses of a full scale three-leaf masonry wall - Francesco Di Michele; Enrico Spacone; Guido Camata; Giuseppe Brando; Anastasios Sextos; Adam Crewe; George Mylonakis; Matt Diez; Luiza Dihoru; Humberto Varum (Bulletin of Earthquake Engineering, 2023)
This paper discusses the main results of a full-scale shaking table test campaign carried out under the auspices of the EU funded research project SERA, whose objective is to investigate the seismic performance of three-leaf masonry walls with weak lime-mortar joints. These masonry walls are widely found in seismic prone regions in the Mediterranean area, thus assessing their behaviour under dynamic actions is an important pre-requisite for the seismic vulnerability evaluation of a plethora of historical centres. The first part of the paper presents a preliminary study on the mechanical properties of the wall component materials that was carried out through an ad-hoc experimental campaign. The outcomes are of particular interest for the characterization of the mortar and of the infill materials, that were designed to reproduce the low strength that is typically found in old masonry buildings. The design of the masonry wall that was tested and the test set-up are presented next. The applied loading protocol consisted of the horizontal component of a ground motion record that is repeatedly applied to the shaking table with increasing intensity. Finally, the main results of the experimental test are discussed. The damage patterns, drift ratios and base shear are presented for the ground motion sequence. The results are also discussed through a dynamic capacity curve that shows the attainment of different limit states with increasing ground motion intensity. A set of nonlinear numerical simulations, both static and dynamic, using a 3D FE model of the wall verify the experimental study as they report good agreement with the experimental tests and exhibit stable numerical behaviour.

Nonlinear finite and discrete element simulations of multi-storey masonry walls - Giuseppe Occhipinti; Ivo Caliò; Antonio Maria D’Altri; Nicola Grillanda; Stefano de Miranda; Gabriele Milani; Enrico Spacone (Bulletin of Earthquake Engineering, 2022)

On the reliability of the equivalent frame models: the case study of the permanently monitored Pizzoli’s town hall - Stefania Degli Abbati; Paolo Morandi; Serena Cattari; Enrico Spacone (Bulletin of Earthquake Engineering, 2022)
This paper presents the comparison of the results of modal and nonlinear analyses carried out on a 2-story masonry building with rigid diaphragms, inspired by the Pizzoli’s town hall (AQ, Italy). The case study is one of the Benchmark Structures (labeled BS6) in the “ URM nonlinear modelling –Benchmark project” funded by the Italian Department of Civil Protection (DPC) within the framework of the ReLUIS projects. The building has been instrumented since 2009 with a permanent monitoring system by the Osservatorio Sismico delle Strutture (OSS) of the DPC and was hit by the 2016/2017 Central Italy earthquake sequence. In the research first phase, modal and nonlinear static analyses were carried out in a blind prediction, without any preliminary calibration of the models, but referring only to commonly made assumptions on materials and modelling. Five computer programs based on the Equivalent Frame Model (EFM) approach were used. Four different structural configurations were considered: with weak spandrels (A), with tie rods coupled to spandrels (B), with RC ring beams coupled to spandrels (C) and with “shear type” idealization (D). In the research second phase, two of the developed EFMs were calibrated in the elastic range using the results of available Ambient Vibration Tests (AVTs). The models were then validated in the nonlinear range by simulating the dynamic response of the structure recorded during the mainshocks of the 2016/2017 Central Italy earthquake. Recorded and numerical results were compared at both the global and local scale.

Assessing community resilience, housing recovery and impact of mitigation strategies at the urban scale: a case study after the 2012 Northern Italy Earthquake - Alberto Basaglia; Alessandra Aprile; Enrico Spacone; Luca Pelà (Bulletin of Earthquake Engineering, 2020)
In this paper, the reconstruction process of a town affected by the 2012 Northern Italy Earthquake is analysed using information published on the town journal. Relevant aspects are highlighted, and the housing recovery is compared with that of a nearby city. Then, a what-if scenario is considered, by proposing a set of seismic mitigation strategies. These strategies are applied to a small sub-system of the city and the variation of the buildings’ vulnerability and expected damage is evaluated using a recently introduced methodology for risk assessments at the urban scale. Finally, a cost–benefit analysis is performed to assess the effectiveness of the proposed strategies. The analysis highlights a significant reduction in the expected damage and socioeconomic impact, as well as an increase in the overall performance of the urban system.

Performance of torsionally eccentric RC wall frame buildings designed to DDBD under bi-directional seismic excitation - Christos Zeris; Alexandros Lalas; Enrico Spacone (Bulletin of Earthquake Engineering, 2020)

Effects of the vertical seismic component on seismic performance of an unreinforced masonry structures - Francesco Di Michele; Cristina Cantagallo; Enrico Spacone (Bulletin of Earthquake Engineering, 2020)

Seismic hazard assessment of northern Pakistan - Muhammad Waseem; Carlo Giovanni Lai; Enrico Spacone (Natural Hazards, 2018)

Seismic safety assessment of existing masonry infill structures in Nepal - Hemchandra Chaulagain; Hugo Rodrigues; Enrico Spacone; Humberto Varum (Earthquake Engineering and Engineering Vibration, 2016)

Earthquake loss estimation for the Kathmandu Valley - Hemchandra Chaulagain; Hugo Rodrigues; Vitor Silva; Enrico Spacone; Humberto Varum (Bulletin of Earthquake Engineering, 2016)

Seismic risk assessment and hazard mapping in Nepal - Hemchandra Chaulagain; Hugo Rodrigues; Vitor Silva; Enrico Spacone; Humberto Varum (Natural Hazards, 2015)

Response reduction factor of irregular RC buildings in Kathmandu valley - Hemchandra Chaulagain; Hugo Rodrigues; Enrico Spacone; Ramesh Guragain; Radhakrishna Mallik; Humberto Varum (Earthquake Engineering and Engineering Vibration, 2014)